The effect of probiotic biscuit on faecal microbiota in malnourished children - Annis Catur, Adi; Kusharto, Clara; Marliyati, Sri Anna Marliyati (Penerbit Universiti Kebangsaan Malaysia, 2022)
A human intervention study on the effect of 90 days supplementation of creamed biscuit with the potential of containing probiotic strain E. faecium IS-27526 at a dose of 108cfu/day on Bifidobacterium in the faecal microbiota of malnourished children under 5 years was conducted. The study was a Randomized Double Blind Placebo Controlled Trial for children under five years old. There were 5 groups with 6 children each: P0 = control biscuit with control cream; P1 = fish and soy protein isolate biscuit with control cream; P2 = control biscuit with probiotic cream; P3 = fish and soy protein isolate biscuit with probiotic cream (every day) and P4 = fish and soy protein isolate biscuit with probiotic cream (every two days). PCR was used to detect Bifidobacterium and Enterococcus faecium in faeces samples. It was concluded after 90 days of supplementation, only 25% of children in the controlled group (P0) harboured Bifidobacterium. In treated groups P1 and P4, the percentage of children positive for Bifidobacterium was approximately 60%, while in groups P2 and P3 the prevalence was 100%. However, the increase of 10% was only demonstrated by P3 as 100% of Bifidobacterium content has been shown in group P2 at the pre-treatment condition. In the controlled group (P0), E. faecium could not be identified either pre or post-intervention, in contrast to the treated groups which showed an increase in some treatments with the highest of 66.7% (group P3). No adverse effect was observed during 90 days of supplementation to children. In conclusion, supplementation of fish and soy protein isolate biscuit and/or probiotic cream every day at a dose of 108cfu/day is considered safe for children under five years old and even increased the number of samples with the presence of bifidobacteria and E. faecium in the fecal microbiota.